Survivors’ Dating and Romantic Relationship Experiences Following Adult Sexual Violence: A Qualitative Interview Study - Stockman, Dagmar (Victims & offenders, 2024)
Survivors of adult sexual violence frequently encounter physical, reproductive, psychological and socio-economic difficulties in the aftermath of sexual violence. However, an in-depth understanding of survivor’s post-assault intimate relationship experiences is lacking. The aim of the current study was to gain a better understanding of survivors’ intimate dating and romantic relationship experiences following sexual violence. Fourteen sexual violence survivors (four men and ten women) completed a semi-structured interview regarding the psychosocial impact of sexual violence including how it affected their intimate relationships. Thematic analysis revealed several key themes including the decision to (temporarily) avoid intimate relationships, changes in the qualities survivors look for in a relationship, the space sexual violence takes up in the relationship, and the healing effects of being in a relationship. Having experienced sexual violence can affect survivors’ post-assault relationship experiences in multiple ways supporting a need for further work focused on understanding how to help survivors manage the relational impact of sexual violence.